Предмет: Алгебра,
автор: Аноним
Найдите у'(-4) если у(x)=(x+3)^7*(x+7)^3
Ответы
Автор ответа:
0
у'(x)=((x+3)⁷*(x+7)³)'=7(х+3)⁶*(x+7)³ +3(х+7)²*(x+3)⁷
у'(-4)=7*(-4+3)⁶*(-4+7)³ +3*(-4+7)²*(-4+3)⁷= 7*(-1)⁶*(3)³ +3*(3)²*(-1)⁷=
= 7*1*27 +3*9*(-1)=7*27 - 27= 27(7-1) =27*6=162
у'(-4)=7*(-4+3)⁶*(-4+7)³ +3*(-4+7)²*(-4+3)⁷= 7*(-1)⁶*(3)³ +3*(3)²*(-1)⁷=
= 7*1*27 +3*9*(-1)=7*27 - 27= 27(7-1) =27*6=162
Похожие вопросы
Предмет: Математика,
автор: dauren270210
Предмет: Геометрия,
автор: samirakhont
Предмет: Математика,
автор: znaniaandznania
Предмет: История,
автор: алла93
Предмет: Математика,
автор: nike238